Management of competitiveness of foreign university in chinese field of education - Li Ming (КНУБА, 2019)
Optimization of educational establishment exchange dealings with rival establishments is the key task of efficient management. This makes it necessary to use the predicting and simulation dynamics of competitiveness pointers in demand to examine alternative approaches for the growth of educational establishments and the selection of optimum situations of its market demeanor. The conception of competitiveness is nevertheless not obviously defined by experts, and differs on the subject zone: enterprise, educational establishments, industry, region, companies, etc. Educational establishments management competitiveness needs the adoption of prudent and scientifically built managerial resolutions. It is essential to take into account a lot of issues that have a important impact on the management progression, the excellence of decisions and outcomes. Multipurpose criteria were used in the simulation model study and the scenarios development for calibration experiments. This makes it possible to solve the inverse problem taking into account several limitations. The obtained results show that the higher educational institution market share can not only not decrease, but it can also double by an increase in the cost of education if the adopted management decisions will be aimed at improving the quality of the provided educational services.
Keywords: education system; promotion; international experience; knowledge management; simulation; managerial cognition; system dynamic modelling; 005.8:378.6(510)